Efektivitas Breathing Exercise Terhadap Penilaian Tingkat Kelelahan Pada Pasien Penyakit Jantung Koroner - Rahmad Wahyudi (NHM PRESS, 2019)
Coronary Heart Disease (CHD)causes the coronary arteries to narrow and theconsumption of O2 to the tissues decreases sothat anaerobic metabolism produces lactic acidwhich causes fatigue as one of the effects orsymptoms of CHD. In the preliminary study,250 people experienced CHD with complaintsof fatigue of 125-150 people. The purpose ofthis study was to analyze differences in the levelof fatigue before and after breathing exercise incoronary heart disease patients in the ICUSYAMRABU Hospital Bangkalan. Method:This study uses an